2008
DOI: 10.1371/journal.pone.0001918
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation Regulates WRN Catalytic Activities and Affects Base Excision DNA Repair

Abstract: BackgroundThe Werner protein (WRN), defective in the premature aging disorder Werner syndrome, participates in a number of DNA metabolic processes, and we have been interested in the possible regulation of its function in DNA repair by post-translational modifications. Acetylation mediated by histone acetyltransferases is of key interest because of its potential importance in aging, DNA repair and transcription.Methodology/Principal FindingsHere, we have investigated the p300 acetylation mediated changes on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 56 publications
1
31
1
Order By: Relevance
“…In our current work, we approached the experiments knowing that numerous DNA replication and repair proteins are acetylated by p300 and that acetylation changes their properties in a way that should promote more efficient strand displacement and consequently more effective repair. 15,17,18,43,51 In our studies, exposing cells to sodium butyrate (deacetylase inhibitor) produced an increase in repair of nicked plasmid DNA in HeLa cells, and also increases in repair of a mismatch and nicks in HeLa and MMR-deficient HCT116 cells. Exposing of cells to garcinol (acetyltransferase inhibitor) inhibited repair of the diagnostic nicksCmismatch-containing plasmid in both cell lines, and also repair of nicked DNA, but only at higher garcinol concentrations in HCT116 cells.…”
Section: Mismatch (mentioning
confidence: 48%
See 4 more Smart Citations
“…In our current work, we approached the experiments knowing that numerous DNA replication and repair proteins are acetylated by p300 and that acetylation changes their properties in a way that should promote more efficient strand displacement and consequently more effective repair. 15,17,18,43,51 In our studies, exposing cells to sodium butyrate (deacetylase inhibitor) produced an increase in repair of nicked plasmid DNA in HeLa cells, and also increases in repair of a mismatch and nicks in HeLa and MMR-deficient HCT116 cells. Exposing of cells to garcinol (acetyltransferase inhibitor) inhibited repair of the diagnostic nicksCmismatch-containing plasmid in both cell lines, and also repair of nicked DNA, but only at higher garcinol concentrations in HCT116 cells.…”
Section: Mismatch (mentioning
confidence: 48%
“…Whereas previous studies showed that LP-BER reactions in vitro were stimulated when performed with whole cells extracts prepared from cells exposed to sodium butyrate, we did not observe such stimulation in our cell-based system. 15 Also, p300-mediated acetylation of different factors involved in BER showed stimulation of synthesis-driven displacement utilized by LP-BER, whereas in our cell-based system depletion of p300 did not affect LP-BER. 15,17,18,43 Specifically, there was no evident effect of acetylation on repair of a mismatch downstream of an 8-oxoG damaged base (GO: MC6).…”
Section: Mismatch (mentioning
confidence: 55%
See 3 more Smart Citations